Systematic identification of the interventional mechanism of Qingfei Xiaoyan Wan (QFXYW) in treatment of the cytokine storm in acute lung injury using transcriptomics-based system pharmacological analyses - Jing-Yi Hou; Jia-Rong Wu; Yi-Bing Chen; Dong Xu; Shu Liu; Dan-dan Shang; Guan-Wei Fan; Yuan-Lu Cui (Taylor & Francis Group, 2022)
Context Acute lung injury (ALI) is a complex, severe inflammation disease with high mortality, and there is no specific and effective treatment for ALI. Qingfei Xiaoyan Wan (QFXYW) has been widely used to treat lung-related diseases for centuries.Objective This study evaluates the potential effects and elucidates the therapeutic mechanism of QFXYW against LPS induced ALI in mice.Materials and methods BALB/c Mice in each group were first orally administered medicines (0.9% saline solution for the control group, 0.5 mg/kg Dexamethasone, or 1.3, 2.6, 5.2 g/kg QFXYW), after 4 h, the groups were injected LPS (1.0 mg/kg) to induce ALI, then the same medicines were administered repeatedly. The transcriptomics-based system pharmacological analyses were applied to screen the hub genes, RT-PCR, ELISA, and protein array assay was applied to verify the predicted hub genes and key pathways.Results QFXYW significantly decreased the number of leukocytes from (6.34 ± 0.51) × 105/mL to (4.01 ± 0.11) × 105/mL, accompanied by the neutrophil from (1.41 ± 0.19) × 105/mL to (0.77 ± 0.10) × 105/mL in bronchoalveolar lavage fluid (BALF). Based on Degree of node connection (Degree) and BottleNeck (BN), important parameters of network topology, the protein-protein interaction (PPI) network screened hub genes, including IL-6, TNF-α, CCL2, TLR2, CXCL1, and MMP-9. The results of RT-PCR, ELISA, and protein chip assay revealed that QFXYW could effectively inhibit ALI via multiple key targets and the cytokine-cytokine signalling pathway.Conclusions This study showed that QFXYW decreased the number of leukocytes and neutrophils by attenuating inflammatory response, which provides an important basis for the use of QFXYW in the treatment of ALI.